A suplementação alimentar de longo prazo com folhas de manjericão (Ocimum basilicum) induz alterações comportamentais e previne o declínio cognitivo associado à idade em camundongos - Pires, Dâmaris Costa Miranda (2022)
Advancing age brings with it some challenges, including changes that occur physiologically, such as cognitive decline, affecting memory, learning and attention. It is known that nutrition can influence the functioning of the central nervous system and its cognitive functions. Common basil (Ocimum basilicum L.) is known for the various health benefits associated with its consumption, including its antioxidant and anti inflammatory effect. Therefore, in the present study, the aim was to analyze and compare the potential beneficial effect of dietary basil ingestion on cognitive functions in aged mice, when mild cognitive decline occurs and in younger animals, when there are still no detectable deleterious functional changes. For this, basil was used as a food supplement for mature adult and elderly adult C57BL/6 female mice. The animals from treated groups received, between four to seven months, a preparation containing a mix of grounded rodent extruded chow (5 g) and an aqueous homogenate of fresh basil leaves (1.2 mg in 10 mL), which was repelleted and oven dried. Later, the mice were cognitively tested in the novel object recognition (NOR), elevated plus maze (EPM) and Morris water maze (MWM). Age-associated cognitive decline, as well as memory and learning were evaluated, and the results, in addition to proving deleterious age dependent cognitive changes in mice, added to a possible anxiolytic effect of aging, demonstrated beneficial effects of basil ingestion, especially in mature adults. In this study, a possible anxiogenic effect of basil in supplemented animals was also evidenced, evident mainly in mature adult animals. Thus, long-term daily ingestion of basil, possibly thanks to its antioxidant and anti-inflammatory activities, can modulate aspects cognitive and behavioral effects, for example, decreasing age-related memory loss, or functioning as a stimulant/anxiogenic agent.